The Popularity Principle and the Distortion of Perception: A Critique of Social Media Algorithms and Their Role in Shaping Public Perception of Indonesian Traditional Arts - Moch. Anil Syidqi; Aris Setiawan (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
Traditional arts in Indonesia face a growing threat not from physical displacement, but from algorithmic distortion. This study examines how social media algorithms shape and distort public perception of Indonesian traditional arts — specifically jaranan and barongan — through the lens of Van Dijck's (2013) popularity principle: the principle that content distribution is determined by interaction volume rather than cultural value. Employing qualitative thematic content analysis, this study analyzes comments on five viral social media videos sourced from YouTube and TikTok, each depicting riots or tension at traditional art performances. Findings demonstrate that the popularity principle operates consistently and cumulatively across all five samples: algorithmically provocative titles, emotional polarization in comment sections, and micro-behavioral signals such as watch duration and replay collectively function as interaction signals that drive the platform to distribute riot content far more widely than culturally substantive footage. The consequences extend beyond perception: event organizers suffer long-term reputational and economic damage, while collective stereotypes — associating jaranan with violence and disorder — become sufficiently entrenched to surface spontaneously in unrelated contexts. A comparative analysis of a Kangen Band concert video reveals that these stereotypes have already achieved the status of cultural reference points. This study argues that strategic resistance is possible: the same algorithmic logic that amplifies negative content can be deployed to circulate culturally rich content, provided that artists, communities, and government commit to producing content designed to generate high-quality interaction. The challenge is to transform social media from a distorting mirror into an instrument of cultural preservation.